From Superdiversity to Social Difference: A Critique of Vertovec’s Paradigm Shift - CHAN, Rachel Suet Kay; Khalid, Kartini Aboo Talib @; A.B, Shamsul (Journal of Ecohumanism, 2024)
Due to Vertovec’s standing as a celebrated social theorist and his influence, we wish to discuss his condensation of sociology’s most crucial concepts to make a convenient model of "the social organization of difference." Having performed a close reading of Vertovec’s works, from the era in which he touted "super-diversity" up to his phrasing of "difference," we have concerns that his body of work leaves out the collective experiences of the "Global South," perhaps unintentionally. In charting this so-called difference, Vertovec limits his scope of discourse to the boundaries of his knowledge. Yet, he is optimistic about positing this model as a one-size-fits-all approach, encompassing the entire human experience. We use examples from the Global South, focusing on the postcolonial societies of Malaysia, Indonesia, and Singapore, to illustrate the gaps in Vertovec’s approach. We do not wish to debunk Vertovec’s ideas entirely; we merely want to signpost the existence of other "different" experiences. Thus, we apply the theories of Southeast Asian scholars to extend this scope of discourse—everyday-defined realities, the social organization of difference, and sociological theory.